The Analysis and Design of Single Plate Framing Connections - Richard, Ralph M.; Gillett, Paul E.; Kriegh, James D.; Lewis, Brett A. (Engineering Journal, 1980)
The single plate framing connection has been considered by designers to be a flexible connection that is economical in both material and fabrication requirements in the erection of steel buildings. Two typical single plate framing connections are shown. In both cases, the connection comprises a single plate, with prepunched bolt holes, that is shop welded to the supporting member. During erection, the beam with prepunched holes is brought into position and field bolted to the framing plate. The standard design procedure for the single plate framing connection is to assume each bolt carries an equal portion of the total shear load and, in agreement with the simple support assumption, that relatively free rotation occurs between the end of the beam and the supporting member. In fact, because of these simplifications the single plate framing connection is often called the "shear tab." Investigations into the structural action, strength, and ductility of the single plate framing connection have been limited and none have satisfactorily proved or disproved the validity of the standard design procedure. Even though this connection has an apparent failure-free performance record, this does not necessarily indicate that good design procedures have been used; the actual load and stress distributions should be understood and the design methods and specifications should reflect the actual structural behavior.